Development, displacement and human rights violations - Tripathi, Sudhanshu (2017)
Every year the lives and livelihoods of more than ten million people across the globe are affected by forced displacement due to infrastructural projects such as dams, mines, industries, power plants, roads, etc. thereby denigrating them from their culture, customs and language by mainstream communities. As a way out, the process of displacement and rehabilitation ought to be executed as a last resort and that, too, be achieved in a planned and more humane manner while taking into confidence the affected people. - Reproduced.
Keywords: Human rights violation; Displacement; Development